2010
DOI: 10.1111/j.1464-5491.2010.03137.x
|View full text |Cite
|
Sign up to set email alerts
|

Does intervention by an allied health professional discussing adherence to medicines improve this adherence in Type 2 diabetes?

Abstract: In conclusion, prior to undertaking an intervention to improve adherence to medicines in Type 2 diabetes, it is necessary to know the baseline level of adherence, and if adherence is already high there is no point in undertaking an intervention. When adherence to medicines is low, it is not clear which interventions will improve adherence, and further studies are needed to clarify this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Across all patient groups, evidence for effective interventions that can support patients in taking their medication is inconsistent and only a minority of trials with a low risk of bias show improvement in adherence and clinical outcomes [4]. Similar findings have been found in systematic reviews focusing on adherence in patients with diabetes [5][6][7][8][9]. Increasingly, interventions are complex, addressing multiple factors, using behavioural, affective and provider-focused components [10].…”
Section: Introductionmentioning
confidence: 60%
“…Across all patient groups, evidence for effective interventions that can support patients in taking their medication is inconsistent and only a minority of trials with a low risk of bias show improvement in adherence and clinical outcomes [4]. Similar findings have been found in systematic reviews focusing on adherence in patients with diabetes [5][6][7][8][9]. Increasingly, interventions are complex, addressing multiple factors, using behavioural, affective and provider-focused components [10].…”
Section: Introductionmentioning
confidence: 60%
“…In the treatment of major depressive disorder, patient compliance was better with once-weekly (85.9%) compared with daily (79.4%) fluoxetine treatment [81], and similar observations were made with bisphosphonate treatment for osteoporosis [82]. Nevertheless, when adherence was poor not all studies demonstrated improvements with less frequent dosing [52]. Although the frequency of dosing appeared to have a significant impact on adherence in most cases, efficacy and safety also remained an important determinant of patient preference [83].…”
Section: Improving Adherencementioning
confidence: 89%
“…There have been many trials of educational intervention methods involving allied health professionals, which have resulted in increased adherence where benefits outweigh the costs associated with the intervention [52, 53]. However, the effects of such interventions are inconsistent between studies and more research of methods to reduce nonadherence and validate cost effectiveness for diabetes is required [54].…”
Section: Factors Influencing Adherencementioning
confidence: 99%
See 1 more Smart Citation
“…Second, psychosocial theory was used in only one of the interventions included in our meta-analysis [37], but a literature review suggests that more effective use of behavior change theory may increase intervention effects [51]. Third, the level of OAD adherence at baseline was already high in 4 of the 10 studies [37 -39,45], which decreased the opportunity to improve adherence with an intervention [52]. Finally, the small effect observed could be explained by poor intervention delivery [53].…”
Section: Discussionmentioning
confidence: 99%